Implementasi Kegiatan Supervisi Akademik di Sekolah - Nashihin, Nashihin; Muhyidin, Muhyidin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
The school is a vehicle or space for the transformation of knowledge by and between school personnel, namely the principal, teachers and students as subjects and objects in the learning process as well as other educational staff who support the smooth running of managerial activities in the school. For the success of learning activities, the competence of the principal as a supervisor in the school is required to provide guidance and direction to teachers through academic supervision activities which are carried out in stages and continuously in accordance with the obstacles experienced by teachers during the learning process. This research aims to explore the implementation of academic supervision. The subjects of this research were teachers at Madrasah Aliyah Ma'arif 7 Banjarwati Paciran Lamongan using purposive sampling techniques. Data collection was carried out using interview, observation and documentation techniques. The research results showed that at this stage activities were carried out, including preparing an academic supervision program plan, preparing academic supervision instruments and socializing the academic supervision program; The stages of implementing activities carried out in academic supervision are pre-observation, observation and post-observation; In the follow-up stage, the activities carried out by the school principal are evaluation and follow-up.